PERAN KOMUNIKASI PEMASARAN DALAM MENINGKATKAN MINAT BELI KONSUMEN DI ERA DIGITAL MENGGUNAKAN BRAND AMBASSADOR - Safitri, Syifa Aulia; Wartika, Ai Ika; Maha Dewi, Aura Pridita; Dwi Yulianto, Marsel; Sundari, Asri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
The COVID-19 pandemic has provided significant challenges for various business sectors, including the apparel and consumption industries. During these conditions, marketing communication plays an important role in helping the company survive and grow again. This study aims to analyze the effectiveness of marketing communication strategies by using brand ambassadors to increase brand awareness in the digital era. The case study was conducted on Yellow Fit Kitchen, a healthy food catering company, which successfully leveraged influencers as brand ambassadors to reach a wider target market. This study uses a qualitative descriptive approach by collecting data through in-depth interviews, documentation analysis, and literature studies. The results of the study show that the selection of the right brand ambassador, based on characteristics such as suitability, credibility, attractiveness, strength, and the ability to transfer brand value, contributes significantly to increasing brand awareness. This strategy is also effective in building relationships with consumers and strengthening the brand image in a competitive market. In conclusion, effective marketing communication through the use of brand ambassadors can be a relevant strategy and have a positive impact in supporting the company's marketing success in the digital era.